Teacher education pedagogies and methodological constructs: or about different ways to approach teacher education - Diaz, Ana Griselda (2014)
This paper plots the methodological constructs identified in different teacher education pedagogies deployed in teacher education settings of Higher Education Institutes in the province of Catamarca. The focus is on showcasing how future teachers are aided -from the methodological constructs of mentors- to make pedagogical decisions and broaden their potential for action during the educational path. The research was conducted from a qualitative approach. Three Higher Education Institutes representing different socio-cultural contexts and educational traditions were selected on the assumption that distinct pedagogies would be found; not only structured on the basis of stereotypical training, but also on the specificity of the disciplinary field. Seventeen semi-structured interviews were carried out and were accompanied by classroom observation of teacher educators in different areas, from distinct disciplinary backgrounds and varied seniority. The qualitative analysis of the data enabled the reconstruction of three typologies that explain the modes in which teacher education is pedagogically configured in the institutes under study as well as the dominant methodological construct that sets up each pedagogical approach. Thus, the pedagogy of ‘modeling’ teaching is based on methodological constructs based on the transmission of disciplinary contents and the instilment of behavior patterns; the ‘traditional’ view is built on methodological constructs elaborated on the basis of disciplinary logic; and the ‘eclectic’ approach is materialized in methodological constructs based on the synthesis of heterogeneous components or constructions grounded on pedagogical abstention.